THE ASIA PACIFIC MANAGEMENT AND BUSINESS APPLICATION: Looking Deeper Toward Management Research and Business Practices in the Growing Economics Regions - Irawanto, Dodi Wirawan (APMBA (Asia Pacific Management and Business Application), 2012)
EDITORIAL The Asia Pacific Management and Business Application: Looking Deeper Toward Management Research and Business Practices in the Growing Economics Regions.